2003
DOI: 10.1371/journal.pbio.0020002
|View full text |Cite
|
Sign up to set email alerts
|

JAMM: A Metalloprotease-Like Zinc Site in the Proteasome and Signalosome

Abstract: The JAMM (JAB1/MPN/Mov34 metalloenzyme) motif in Rpn11 and Csn5 underlies isopeptidase activities intrinsic to the proteasome and signalosome, respectively. We show here that the archaebacterial protein AfJAMM possesses the key features of a zinc metalloprotease, yet with a distinct fold. The histidine and aspartic acid of the conserved EXnHS/THX7SXXD motif coordinate a zinc, whereas the glutamic acid hydrogen-bonds an aqua ligand. By analogy to the active site of thermolysin, we predict that the glutamic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(223 citation statements)
references
References 37 publications
9
214
0
Order By: Relevance
“…Indeed, there may be a difference among DUBs in terms of their mode of action: one group may function by direct recognition of their substrates, while the other group, including the JAMM domain-containing isopeptidases, may function as a constituent of a complex (Amerik and Hochstrasser, 2004). The unique structures of the catalytic regions of the DUBs, as well as the presence of specific sets of interaction domains in the different DUBs may explain such differences (Ambroggio et al, 2004). Interestingly, unlike the ESCRT-0, -I, and -II components, ESCRT-III constituents seem to lack previously identified ubiquitin-binding motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there may be a difference among DUBs in terms of their mode of action: one group may function by direct recognition of their substrates, while the other group, including the JAMM domain-containing isopeptidases, may function as a constituent of a complex (Amerik and Hochstrasser, 2004). The unique structures of the catalytic regions of the DUBs, as well as the presence of specific sets of interaction domains in the different DUBs may explain such differences (Ambroggio et al, 2004). Interestingly, unlike the ESCRT-0, -I, and -II components, ESCRT-III constituents seem to lack previously identified ubiquitin-binding motifs.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, we prepared an enzymatically inactive AMSH, AMSH E280A , basing our construct design on a report in which replacement of a glutamic acid residue (E20) by alanine within the JAMM motif of the Archaeoglobus fulgidus AfJAMM protein completely abolished the catalytic activity (Ambroggio et al, 2004). To verify that the AMSH E280A mutant possessed no DUB activity, we performed an in vitro deubiquitination assay.…”
Section: Amsh Associates With the Escrt-iii Protein Chmp3mentioning
confidence: 99%
“…JAMMs contain a signature 'H-x-H-P-x[6]-S-x[2]-D' motif within the MPN domain that, through its invariant His and Asp residues, coordinates a zinc atom, which is required for activity (12,47,56,169,170,225,284). JAMMs are generally incorporated into large multimeric complexes such as the proteasome lid complex (POH1/Rpn11), COP9 signalosome (CSN5), and the endocytic ESCRT machinery (AMSH) (39,46,72).…”
Section: E Jamm Familymentioning
confidence: 99%
“…Nevertheless, CSN5 or RPN11 protein alone are inactive in the absence of association with CSN or the proteasome, respectively. Recently, the crystal structure of an Archaeoglobus fulgidus JAMM domain-containing protein (AF2198) has been determined, which confirmed that a zinc ion was present in the catalytic center (Tran et al, 2003;Ambroggio et al, 2004). However, the CSN5-dependent metalloprotease activity is not essential in fission yeast, where no obvious phenotype has been detected in the csn5 mutant Mundt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%